Individual differences in temporal order judgment - Leah Fostick; Moti Zwilling; Harvey Babkoff (Scientific Reports)
Abstract Large individual differences can be observed in studies reporting spectral TOJ. In the present study, we aimed to explore these individual differences and explain them by employing Warren and Ackroff (1976) framework of direct identification of components and their order (direct ICO) and holistic pattern recognition (HPR). In Experiment 1, results from 177 participants replicated the large variance in participants’ performance and suggested three response patterns, validated using the K-Means clustering algorithm. In Experiment 2, the introduction of three tone-pairs to 90 participants, as opposed to a single pair, markedly decreased the propensity of participants to utilize HPR. Experiment 3 assessed 85 participants and demonstrated that diotic presentations significantly reduced the prevalence of HPR utilization. These results confirmed that direct ICO is used mainly when stimuli are difficult to group, and when grouping is possible, HPR is used. The results also show that these strategies are flexible and change according to the experimental manipulation. Spectral TOJ provides an opportunity to observe individual differences in auditory perception and facilitates the investigation of the diverse psychoacoustic cues underlying its performance.